An Empirical Path-Loss Model for Wireless Channels in Indoor Short-Range Office Environment - Ye Wang; Wen-jun Lu; Hong-bo Zhu (International Journal of Antennas and Propagation)
A novel empirical path-loss model for wireless indoor short-range office environment at 4.3–7.3 GHz band is presented. The model is developed based on the experimental datum sampled in 30 office rooms in both line of sight (LOS) and non-LOS (NLOS) scenarios. The model is characterized as the path loss to distance with a Gaussian random variable X due to the shadow fading by using linear regression. The path-loss exponent n is fitted by the frequency using power function and modeled as a frequency-dependent Gaussian variable as the standard deviation σ of X. The presented works should be available for the research of wireless channel characteristics under universal indoor short-distance environments in the Internet of Things (IOT).